Production Technology and Quality Assessment of Microcapsules of Lycopus europaeus L. Herb Dry Extract - O. A. Semkina; O. M. Beloshapkina (Регуляторные исследования и экспертиза лекарственных средств, 2024)
SCIENTIFIC RELEVANCE. The high hygroscopicity and poor flowability of herbal extracts complicate the manufacturing of medicinal products based on these active substances. Microencapsulation of dry herbal extracts reduces their hygroscopicity, improves their flowability, and expands their applicability. Further development of medicinal products based on herbal extracts requires a comparative analysis of the relationships between the quality of microparticles and the selected microencapsulation method.AIM. This study aimed to conduct a practical evaluation of a previously developed microcapsule production technology and to evaluate the quality of a microencapsulated dry extract of Lycopus europaeus L. herb.MATERIALS AND METHODS. The study analysed a dry extract of Lycopus europaeus herb with a thyrostatic effect, which was microencapsulated by dispersion. A film-forming agent was used to form the microcapsule shells (gelatine, grade P-11). The microcapsules were characterised by the following pharmacopoeial quality parameters: particle size, moisture content, and flowability. The qualitative and quantitative analysis of the dry extract of Lycopus europaeus herb used thin-layer chromatography and spectrophotometry.RESULTS. The study identified the optimum ratios for Lycopus europaeus herb dry extract and excipients as well as the procedure for ingredient addition during the microencapsulation process. The resulting microcapsules were homogeneous particles with a diameter of 50–300 µm, a moisture content of 3.21±0.12%, and a good flow. The encapsulation efficiency of the dispersion method reached 95.0±1.3%. In contrast to non-encapsulated dry extract particles, the particles of microencapsulated Lycopus europaeus herb dry extract had a spherical shape, smooth surface, and improved technological properties.CONCLUSIONS. The authors developed a microencapsulation technology for Lycopus europaeus herb dry extract. The study results confirmed the efficiency of the microencapsulation method in reducing the hygroscopicity of Lycopus europaeus herb dry extract, increasing its stability during storage, and optimising the further development of dosage forms.